Pengaruh Penggunaan Media Game Kuis Kahoot terhadap Minat Siswa pada Mata Pelajaran Matematika di Kelas XI IPS SMA N 2 Pasaman Tahun Pelajaran 2022/2023 - Silfi Anggraeni; Aniswita Aniswita; Isnaniah Isnaniah; Risnawita Risnawita (Departement of Mathematics Education, 2024)
This research is motivated by lack of interest in student’s learning in mathematics and the lack of uses of varied learning media by the teacher. Based on these problems, researchers are interested in examining the effect of using the Kahoot quiz game media on student’s learning interest in mathematics in classs XI IPS SMA N 2 Pasaman. This type of research ia an expeerimental research with one group pretest-posttest research design. From the total population of 4 classes consisting of 120 students, a sample was taken of 1 class consisting of 30 students from class XI IPS 2 SMA N 2 Pasaman. Sampling using random sampling technique. The instrument used is a questionnaire of student’s interest in learning mathematics. The research data is the form of pretest data and posttest data. Based on the result of data analysis it was obtained that tcount = 2,569 > ttable = 1,699 wich resulted in rejection of H0. After calculating using the SPSS application was obtained significance value of <0,05 wich caused rejection of H0. So there is influence of the Kahoot quiz game media on student’s learning interest in mathematics in class XI IPS SMAN N 2 Pasaman.